2015
DOI: 10.1016/j.physio.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in delivery of respiratory treatments by on-call physiotherapists in mechanically ventilated children: a randomised crossover trial

Abstract: Clinicaltrials.gov NCT01999426.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
6
0
3
Order By: Relevance
“…6 In a separate study, the clinically important differences between the treatment provided by the non-respiratory and specialist respiratory physiotherapists illustrates the significance of training and proficiency of non-respiratory on-call physiotherapists, particularly in delivering physiotherapy treatments in the critical care environment. 7 Inferring from these ideas, it is therefore only sensible to establish the minimum standards of clinical practice relevant to the local critical care settings. Furthermore, there are currently no standardised local training guidelines to acquaint physiotherapists with this highly specialised domain.…”
Section: Introductionmentioning
confidence: 99%
“…6 In a separate study, the clinically important differences between the treatment provided by the non-respiratory and specialist respiratory physiotherapists illustrates the significance of training and proficiency of non-respiratory on-call physiotherapists, particularly in delivering physiotherapy treatments in the critical care environment. 7 Inferring from these ideas, it is therefore only sensible to establish the minimum standards of clinical practice relevant to the local critical care settings. Furthermore, there are currently no standardised local training guidelines to acquaint physiotherapists with this highly specialised domain.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim deve ser realizada de forma humana e sutil. Andreazza et al (2019), Shannon et al (2015), para que seja feita de forma a trazer benefícios para os neonatos o fisioterapeuta deve ter conhecimento e treinamento para que assim seja aplicada de forma correta.…”
Section: Discussionunclassified
“…The perceived lack of consistency in the level of clinical competence, required skills and content of training between hospitals is compounded by the absence of a national policy, procedure or clinical framework for physiotherapists working in critical care. Previous research found clinically important differences in the treatment administered by the critical care physiotherapist compared with the on-call physiotherapists including duration of assessment, treatment selection and execution [3]. This indicates a need to standardise training.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted in South Africa [7] investigated the minimum standards required for physiotherapists working in critical cares, adopting qualitative methodology completing focus group sessions with experienced physiotherapists, both clinicians and academics [8]. While the study conducted in South Africa [7] differed in design to the Australasian, UK and Japanese studies [3][4][5] all studies identified the need to develop national standards and clinical frameworks to support education and reduce variability in clinical practice.…”
Section: Introductionmentioning
confidence: 99%